Physicochemical Properties, Bioactive Compounds Degradation Kinetics, and Microbiological Counts of Fortified Pomegranate Gummy Candy (GC) during Ambient Storage - Qi, Ng An; Hasnan, Noor Zafira Noor; Basha, Roseliza Kadir; Alyas, Nur Diyana; Zulkifli, Nurin Izzati Mohd (Department of Agro-industrial Technology, University of Brawijaya, 2023)
Abstract This study explored the potential of fortified pomegranate gummy candies (GC) as a solution for insufficient vitamin C and phenol intake. It entailed two objectives: assessing the impact of ambient storage (20±2 ℃) on various GC properties and developing kinetic models to predict vitamin C and phenol degradation during storage. The study involved the preparation of GC using a modified formulation and examined moisture content, water activity, texture, vitamin C, total phenolic content, and microbiological counts during 15-day-storage. Findings revealed that the moisture content decreased from 21.82% to 13.41%, potentially affecting texture. Water activity remained high (0.84-0.86), posing potential microbiological risks. The textural analysis indicated high hardness, springiness, gumminess, and chewiness, which may impact consumer acceptance. Adhesiveness remained minimal. Vitamin C decreased from 2,176.90 mg AA/100g to 1,419.10 mg AA/100g, possibly influenced by moisture and oxygen. Phenolic content decreased from 2,845.97 mg GAE/100g to 2,183.70 mg GAE/100g, remaining remarkably high. Kinetic modeling revealed that zero-order kinetics best described degradation, with constant degradation rates. In conclusion, fortified pomegranate GC demonstrate potential as functional food. However, further research is necessary to optimize texture properties, improve formulation and understand complex interactions between gelatin and phenolic compounds for enhanced consumer acceptance and health benefits.Keywords: gummy candy, kinetic modelling, phenol, physicochemical properties, vitamin C AbstrakStudi ini mengeksplorasi potensi gummy candy (GC) fortifikasi buah delima sebagai solusi kekurangan asupan vitamin C dan fenol. Penelitian ini bertujuan untuk menilai dampak penyimpanan suhu ruang (20±2 ℃) pada berbagai sifat GC dan mengembangkan model kinetik untuk memprediksi degradasi vitamin C dan fenol selama penyimpanan. Pembuatan GC pada penelitian ini menggunakan formulasi yang dimodifikasi dan kemudian dilakukan pemeriksaan kadar air, aktivitas air, tekstur, vitamin C, kandungan fenolik total, dan jumlah mikrobiologis selama 15 hari penyimpanan. Hasil menunjukkan bahwa di akhir penyimpanan, kadar air menurun dari 21,82% menjadi 13,41%, berpotensi memengaruhi tekstur. Aktivitas air tetap tinggi (0,84-0,86), sehingga menimbulkan potensi risiko mikrobiologis. Analisis tekstur menunjukkan kekerasan, springiness, gumminess, dan chewiness yang tinggi, yang mungkin berdampak pada daya terima konsumen. Daya rekatnya tetap rendah. Vitamin C menurun dari 2.176,90 mg AA/100g menjadi 1.419,10 mg AA/100g, kemungkinan dipengaruhi oleh kelembapan dan oksigen. Kandungan fenolik menurun dari 2.845,97 mg GAE/100g menjadi 2.183,70 mg GAE/100g, namun masih sangat tinggi. Pemodelan kinetik mengungkapkan bahwa kinetika orde nol paling tepat menggambarkan degradasi, dengan laju degradasi yang konstan. GC yang difortifikasi buah delima menunjukkan potensi sebagai pangan fungsional. Penelitian lebih lanjut diperlukan untuk mengoptimalkan sifat tekstur, meningkatkan formulasi dan memahami interaksi kompleks antara gelatin dan senyawa fenolik untuk meningkatkan daya terima konsumen dan manfaat kesehatan.Kata Kunci: fenol, gummy candy, pemodelan kinetik, sifat fisikokimia, vitamin